Exploring aesthetic experiences of females: Affect-related traits predict complexity and arousal responses to music and affective pictures. (15th April 2018) - Marin, Manuela M.; Leder, Helmut
Abstract: Empirical studies testing Berlyne's (1971) psychobiological model have led to conflicting results, and individual differences have been proposed as a possible explanation. We explored whether top-down influences related to personality may play a role and studied how affect-related personality traits are related to complexity and arousal responses. Two hundred and six females rated either affective environmental scenes, environmental scenes converted into cartoons, or representational paintings (Study 1). Another group of 77 females rated excerpts of piano music (Study 2). We assessed trait emotional intelligence (EI), stress reactivity (SR), empathy (Study 1), emotional self-efficacy (Study 2) as well as engagement with art and music. Linear mixed-effects modelling revealed that affect-related traits emerged as significant predictors in all visual complexity and arousal models, except for the complexity model of environmental scenes. SR predicted arousal induced by environmental scenes, but not by cartoons and paintings, for which an interaction between trait EI and empathy was found. Musical sophistication predicted musical complexity, and the complexity and arousal models comprised interactions between trait EI, SR and emotional self-efficacy. Affect-related traits should be integrated into arousal-based theories of aesthetic experiences, and their impact on perceived complexity and felt arousal varies across stimulus categories. Highlights: Trait EI, empathy and stress reactivity predict aesthetic responses in females. Affective traits predict complexity and arousal responses to pictures and music. General art interest did not predict perceived visual complexity and felt arousal. Musical sophistication predicted musical complexity but not arousal. Affect-related traits and measures of interest were not correlated.